Ocean's eleven (1960) [videorecording (DVD)] - Milestone, Lewis, 1895-1980; Milestone, Lewis, 1895-1980; Sinatra, Frank, 1915-1998; Martin, Dean, 1917-1995; Davis, Sammy, Jr., 1925-1990; Lawford, Peter, 1923-1984; Dickinson, Angie (Warner Home Video, 2001)
The place is Las Vegas. The time: Midnight, New Year's Eve. Danny Ocean (Sinatra) and 10 of his ex-commando buddies get ready to rob the vaults of 5 casinos simultaneously!